Personal information retrieval: smartphones vs. computers, emails vs. files. (August 2018) - Bergman, Ofer; Yanai, Nimrod
Abstract Millions of people retrieve their emails and files using their smartphones, yet smartphone retrieval of such personal information has never been studied or compared to retrievals from PCs. In our within-subjects study, we compared the retrievals of our 57 participants in four conditions: files using PCs, emails using PCs, files using smartphones, and emails using smartphones. Our results indicate that when using smartphones, retrievals were significantly less successful and efficient than when using PCs, casting doubt on the implicit assumption that the use of these devices is equivalent. Our results also indicate that participants used the search facility for emails about seven times more than for files, which can encourage vendors to invest more efforts in improving email search engines and file navigation systems. Finally, we found that the tendency to search shows interpersonal differences but consistency across different situations for the same individual and therefore can be regarded as a personal trait. Future research can attempt to explain the search tendency trait in terms of cognitive abilities and personality traits, incorporating it to well-established theories. This may pave the way to a new trait-related theory in the field of information science.